Arterio-venous malformations of the ear: Description of distinct anatomical presentation and multidisciplinary management approach. Issue 7 (July 2021) - Bulstrode, Neil W.; Lese, Ioana; Aldabbas, Mohammed; Glover, Mary; Robertson, Fergus; Rennie, Adam
Summary: Background: Arterio-venous malformations (AVMs) of the ear are a rare entity and their management should be decided in a dedicated multidisciplinary team (MDT) setting. The aim of this study is to describe the distinct anatomical patterns of the auricular AVMs in our unit and propose a combined interventional radiological and surgical approach. Materials and methods: All consecutive patients presenting with AVMs of the ear and reviewed by the Vascular Anomalies MDT between 2014 and 2019 were included in this study. Signs, symptoms, diagnostic investigations and operative findings were collected prospectively. Results: After reviewing our nine patients, we identified four anatomical patterns of auricular AVMs: I: involves just a component of the ear and should undergo embolization followed by excision and reconstruction without significant loss of form; II: affects the superior two-thirds of the ear, sparing the lobule and part of the conchal bowl; these patients should undergo embolization, excision and monitoring before formal reconstruction of the ear is offered; III: involves the entire ear and should undergo embolization and pinnectomy; if there is no recurrence, the patients can be offered either a carved-rib cartilage reconstruction or a prosthesis, depending on the quality of the surrounding soft-tissues; IV: involves the ear and surrounding tissue, making surgical management and subsequent reconstruction extensive. Conclusion: The management of auricular AVMs is based on the extent of the ear involved. We feel that our combined interventional radiological and surgical approach will aid the management of these complex patients.